2011
DOI: 10.1158/1055-9965.epi-11-0400
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Adipophilin as a Potential Plasma Biomarker for Colorectal Cancer Using Label-Free Quantitative Mass Spectrometry and Protein Microarray

Abstract: Background: The aim of this study was to identify a new plasma biomarker for use in early detection of colorectal cancer.Methods: Using the combination of hollow fiber membrane (HFM)-based low-molecular weight protein enrichment and two-dimensional image converted analysis of liquid chromatography and mass spectrometry (2DICAL), we compared the plasma proteome of 22 colorectal cancer patients with those of 21 healthy controls. An identified biomarker candidate was then validated in two larger cohorts [validati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 40 publications
0
50
0
Order By: Relevance
“…Plasma samples for RPPAs (set for RPPAs) and LC-MS/MS analysis (early-stage set and all-stage set) listed in Table 1 were collected from seven medical institutions as part of the “Third-Term Comprehensive Control Research for Cancer” project and stored at -80°C at the National Cancer Center Research Institute until analysis as described previously [17,18,28]. All study subjects were finally diagnosed and classified at each institution before RPPA and LC-MS/MS analysis were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma samples for RPPAs (set for RPPAs) and LC-MS/MS analysis (early-stage set and all-stage set) listed in Table 1 were collected from seven medical institutions as part of the “Third-Term Comprehensive Control Research for Cancer” project and stored at -80°C at the National Cancer Center Research Institute until analysis as described previously [17,18,28]. All study subjects were finally diagnosed and classified at each institution before RPPA and LC-MS/MS analysis were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Adipophilin is one of the important players in lipid metabolism, responsible for storage of lipid droplets in all types of cells [4, 5]. Some recent studies show that many tumors overexpress adipophilin [6–22], especially those with clear cell histology [10, 11]. Several small reports showed that renal cell carcinoma (RCC) cells also overexpress adipophilin [10, 11, 2327] and one major study [24] reported the prognostic role of this biomarker in clear cell subtype on transcript level.…”
Section: Introductionmentioning
confidence: 99%
“…Lung tumours exhibit abnormalities in vessels structure that limit the supply of nutrients and leads to hypoxia; therefore, metabolic processes such as carbohydrate and lipid metabolism must be altered in order to support cell growth [17]. Indeed, lipid metabolism has been implicated in lung cancer progression [18], while other studies have reported that PLIN2 is overexpressed in breast and colorectal cancers and malignant melanoma [9][10] and promoted ccRCC proliferation by inhibiting ER stress through increased lipid storage [11]. PLIN2 expression in a subset of lung adenocarcinoma cases is associated with the presence of wild-type EGFR and reduced overall survival [12].…”
Section: Discussionmentioning
confidence: 99%
“…PLIN1 is primarily expressed in adipose and steroidogenic cells, while PLIN2 is ubiquitously expressed and functions as the predominant LD coat protein in non-adipose tissues [8], playing a key role in fatty acid uptake, LD formation, and lipid storage. Previous studies have shown that PLIN2 is upregulated in many cancers, including clear cell renal cell carcinoma (ccRCC), malignant melanoma, and colorectal cancer [9][10]. Hypoxia-inducible factor (HIF)-2α was found to promote PLIN2 expression and lipid storage in ccRCC cell lines, which was required for endoplasmic reticulum (ER) homeostasis and resistance to cytotoxic ER stress [11].…”
Section: Introductionmentioning
confidence: 99%